MENGUJI RELEVANSI TEORI “SUPPLY CREATES ITS OWN DEMAND” PADA PASAR TENAGA KERJA DI INDONESIA (JEB17 : Jurnal Ekonomi dan Bisnis, 2023)
Jean-Baptiste Say is one of the economists with a classical school of thought who is famous for the theory of 'supply creates its own demand' or also known as Say's Law of Market. Market Law Theory Let's say this is motivated by a refutation of the mercantilist doctrine, which says money, the market balance, will produce wealth and economic growth. Say trying to create that creates money, but rather a product of goods and services. In Indonesia itself, one of the problems that never comes is employment. The purpose of this paper is to find out the relevance of the theory of “supply creates its own demand” in the labor market in Indonesia. The research method used is qualitative by analyzing data from official sources and collecting from journals, books, and previous research sources. Supply theory creates its own demand may be relevant depending on the conditions at hand. However, regardless of whether it is relevant or not, intervention from the Government in Indonesia is indispensable in maintaining economic stability. Keyword: Jean Baptiste Say, supply creates its own demand, labor force, Indonesia, say’s law of the market, classical economic